PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS TUTORIAL BAGI MAHASISWA TEKNIK MESIN STT PLN - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
Tutorial method is a way of delivering learning materials that have been developed in the form of modules for students to learn independently. Students can consult about the problems and progress encountered periodically. Many limitations teacher, in choosing the right method of teaching cause lecturer difficult to realize the demands of the students in this teach. Acceleration we can see at universities around us, still very much a lecturer who uses teaching methods in a conventional way, such as lectures, notes, summarizes and etc. Research aims to determine the effectiveness of the use of the tutorial method of teaching in the department of mechanical engineering. This study uses research and development (Research and Development), the stage of preliminary studies carried out by applying a qualitative descriptive approach. The development phase is done by trial limited to the conventional model of teaching faculty by applying experimental methods (Single One Shot Case Study) After no improvement on the limited test then continued with a broader test of the experimental method in the form of groups (one group pretest-posttest). The latter is a tutorial teaching model validation methods eksprimen. The result of research shows that tutorial teaching methods more effective than the old teaching methods, both on the speed aspect of students' understanding of the lecture material, creativity, and student results.